LIFELONG EDUCATION AS A KEY FACTOR OF THE TRANSFORMATION AND DEVELOPMENT OF THE HUMAN CAPITAL’S POTENTIAL - Tatarinceva, Anna; Gode, Ina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Actuality of the proposed research is caused by the facts that the rapid development of market relations in the Latvian economy and a high level of life in the “old countries” of the European Union affect the outlook of the majority of young people in Latvia. There is a tendency to reduce the motivation for obtaining fundamental education by giving preference to acquisition of certain professional skills allowed to get ‘quick money”. The Object of the research is the transformation process of students’ beliefs, values, competences, experience during their lifelong learning. The Aim of the research in to analyze the influence of lifelong education on the transformation of students’ beliefs, values, competences and experience. The Methods of the research are the following: 1.theoretical methods: the theoretical analysis of the scientific literature on the given problem; 2.quantitative methods: questionnaires; 3.the empirical analysis of the survey’s answers given by students of Latvian higher and vocational schools about the transformation of their beliefs, values, competences, experience during the process of lifelong learning. The Baltic International Academy (Riga, Latvia), The Latvian Agricultural University and the Jelgava College (Jelgava, Latvia) were used as the experimental Base of the research.